Development of a Simple and Sensitive Terbium SensitizedFluorescence Method forDetermination of Epinephrine andNorepinephrine in Serum: Determination of nor/epinephrine in serum - Shaghaghi, Masoomeh; L. Manzoori, Jamshid; Jouyban, Abolghasem (Iranian Journal of Pharmaceutical Sciences, 2007)
Asimple, rapid, selective and highly sensitive fluorimetric method fordetermination of two catecholamines, i.e. norepinephrine (NE) and epinephrine (EP),in serum samples was developed. The method is based on the fluorescencesensitization of terbium (Tb3+) by complexation with both catecholamines in thepresence of lanthanum (La3+), as a co-cation, and in a Na2SO3solution (chemicaldeoxygenating agent), which fluoresces intensely with an emission maximum at 545nm when excited at 312 nm. We found that fluorescence enhancement effects wereobserved when La3+was added to the system (co-luminescence effect). In thepresence of this element the fluorescence of the Tb-catecholamines system wasenhanced by a factor of about 15 compared with that of the system without La3+.Optimum conditions for the formation of the complexes were investigated. Underoptimum conditions, a linear relationship was obtained between the fluorescenceintensity and catecholamines concentration in the range of 2.5×10-3to 0.22 μg.ml-1. The detection limits were 0.59 and 0.58 μg.l-1for EPand NE, respectively.Relative standard deviation (RSD) values for two compounds were in the range of1.2-2.1% indicating excellent reproducibility. The proposed method was successfullyapplied to the determination of EPand NE in spiked serum samples after deproteiniza-tion of the samples with acetonitrile. Analytical recoveries from treated serumsamples were in the range of 95-105%.